Assessment of analytical formulations for the ULS resistance verification of structural glass elements accounting for the effects of different load durations. (August 2017) - Bedon, Chiara; Amadio, Claudio
Abstract: Glass is an increasingly used material in construction and buildings. Despite its large application as load-bearing construction material, several aspects related to safe and optimal design are still under investigation and exploration, towards the full implementation of standardized and conservative rules of practical use. One of the main concerns in the design of this typically tensile brittle material is given by the rational estimation of static fatigue phenomena, under the effects of multiple design loads. In this paper, careful consideration is paid to the Ultimate Limit State (ULS) resistance verification of structural glass elements under a combination of variable loads with assigned duration. Taking advantage of past literature contributions and existing design standards for glass, an assessment of several available formulations to account for the cumulative stress effects of combined design loads is first carried out by means of selected case studies and extended parametric analytical calculations. Based on the obtained results, an alternative, simplified but practical and rather accurate - compared to the exact theoretical model - linear formulation is also finally proposed to account for static fatigue phenomena in load-bearing glass elements.